Development of milling ancilliary compatible with two-stroke power saw engine for short log conversion (2010)
Chainsaw milling is an inevitable means of preventing quantum wastage of valuable and scarce wood resource in un-accessible locations. Milling attachment (MA) was developed for a two stroke power chainsaw to reduce milling difficulties, risk and wastage. Operators of power-saw (90) were randomly selected and interviewed to elicit information on profile and limitations of chainsaw milling. Milling ancillary was developed for two stoke power-saw engine (T-S-PSE) with power to weight ratio rating and guide bar length of 1.5g/w and 75.0cm respectively. Results showed that only 33.3% had formal training while 65.6% were hitherto either unskilled labourers involved in logging activities or sawmill sawyers. About 57.8% respondents own their machine with about 32.7% of them engaged in log merchandize. The average age on chainsaw milling was 15years and it was a means of livelihood for only about 64.4% of the total respondents. This group of respondents is often engaged throughout the year, worked at both open field and forest reserves in Oyo, Osun and Ogun States. The criteria for service charge include activities, log girth, location and environment. MA suitable for use with the described T-S-PSE for milling 500mm maximum log diameter was developed at the cost of four thousand nine hundred naira (N4900). The study was able to develop MA compatible with T-S-PSE and with 69% performance efficiency.